Tryptophan N1-Alkylation: Quick and Simple Access to Diversely Substituted Tryptophans - Junk, Lukas; Papadopoulos, Emanuel; Kazmaier, Uli (Synthesis, 2021)
The diversification of amino acid sidechains is a major challenge in the synthesis and derivatization of peptides for pharmaceutical applications. We herein present a new protocol to alkylate the indole-nitrogen (N1) of Nα-protected tryptophans. This method provides quick and epimerization-free access to tryptophan derivatives, which can directly be incorporated into peptides. Depending on the functionalities introduced in the side chain, different options for the late-stage modification of peptides are possible.
Keywords: tryptophan; N-alkylation; amino acids; late-stage diversification; peptide modification